Teoria della turbolenza lectures given at a summer school of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Varenna (Como), Italy, September 1-9, 1957 - Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) : (C.I.M.E. Summer Schools ;, 2011)
J. Kampé de Fériet: Problèmes mathématiques de la théorie de la turbulence homogéne -- L. Dubreil-Jacotin: Sur les axiomes des moyennes -- J. Arbault: Transformations de Reynolds sur un ensemble fini -- O. Björgum: On the possibility of a mathematical theory of shearflow turbulence -- C. Ferrari: Turbolenza di parete -- C. Agostinelli: Turbolenza in magneto-idrodinamica -- J. Laufer: The hot-wire techniques in supersonic research -- R. Wille, O. Wehrmann: Hitzdrahtmessungen in freien Grenzschichten -- W. Tollmien: Miscellen aus der Turbulenzforschung.